AB1152 Musculoskeletal manifestation of diabetes mellitus is highly prevalent and is associated with poor diabetic control. (12th June 2018) - Khan, K.; Ali, K.; Farrukh, S.; Haroon, M.
Abstract : Background: Diabetes mellitus is one of the most common medical conditions all over the world. A variety of musculoskeletal (MSK) conditions have been associated with diabetes mellitus (DM). These MSK symptoms are important to recognise because these can respond to treatment. Estimates of the prevalence of MSK problems in patients with DM vary depending upon the definitions used for the problems and the study population with diabetes, which can range from a primary care cohort to patients with severe diabetes in a specialised referral setting. Objectives: The objectives of our study were: 1) to investigate the prevalence of musculoskeletal complications of diabetes in a consecutive cohort of patients attending a secondary care endocrinology clinic; and 2) to identify clinical associations of such musculoskeletal complications by examining likely contributing features including patient characteristics, life style factors and features of underlying diabetic disease. Methods: The study participants were all consecutive patients attending endocrinology clinics of University Hospital Kerry for the management of their DM. Patients with chronic inflammatory arthritis or chronic autoimmune diseases were also excluded. This was a questionnaire-based study and was carried out in two steps. The first step involved having a short interview and assessment of the patient, and in the second step their clinical records were reviewed to populate clinical parameters. The clinical variables studied were gender, smoking habits, body mass index (BMI), units of alcohol intake per week, smoking habits, type of DM, duration of DM, medications used for DM, employment status and also their current HbA1c blood results. End organ complications of DM were also included, Moreover, personal history of cardiovascular risk factors and diseases were also recorded, Since there is a long list of rheumatologic manifestations which are potentially associated with DM and many of them are less sensitive and specific for DM, we choose to study the 4 common DM-associated rheumatologic presentations (Stiff hands, Carpel Tunnel Syndrome, Charcot joint, bilateral shoulder rotator cuff tendinopathy). Moreover, importantly, only patients with the musculoskeletal symptoms lasting for >3 months were included in the analysis. These 4 DM-associated musculoskeletal diseases are labelled as DM-MSK diseases. Results: A total of 250 patients [mean age 66±16 years; 58% male; mean duration of DM 13±10 years; mean BMI of 27.5±6] were evaluated. DM-MSK diseases were present in 37.6% (n=94) of the entire cohort. On univariate analysis, patients with older age, type-2 DM, using hypoglycaemic agents, hypertension, ischaemic heart disease, peripheral vascular disease, cerebrovascular accident, congestive heart disease, and patients with renal involvement had significantly higher prevalence of DM-MSK symptoms. However, on multivariate analysis (table-3), poor diabetic control as reflected by higher HbAIC levels, presence of diabetic kidney disease and advancing age were associated with the presence of DM-MSK symptoms. Conclusions: We conclude that MSK manifestations of DM are very common but unfortunately these remain poorly recognised and continue to cause significant disabilities. Similar to the microvascular and macrovascular complications, MSK manifestations are associated with poor diabetic control. Disclosure of Interest: K. Khan: None declared, K. Ali: None declared, S. Farrukh: None declared, M. Haroon Grant/research support from: abbvie, Pfizer, Speakers bureau: abbvie, Pfizer, UCB